Mardonov Jamshid Normurotovich - Mardonov Jamshid Normurotovich; Khudayberganova Nasiba Shakirovna; Abdullaeva Mokhima Abdullaevna; Palvonniyozov Khumoyun Gayratjon ugli; Gaybullayev Temurbek Zokir ugli; Yigitaliev Sardor Khusanbaevich; Khasanov Khamdam Kamiljanovich (Western European Studies, 2026)
Despite the widespread adoption of minimally invasive surgical techniques, postoperative complications associated with impaired implant integration and infectious processes remain a major clinical challenge. The interaction between implanted biomaterials and surrounding tissues plays a pivotal role in regulating inflammatory responses, tissue remodeling, and long-term surgical outcomes. Objective. To experimentally substantiate the effectiveness of the combined use of composite biomaterials and synthetic implants under sterile and infected conditions. Methods. An experimental study was conducted using laboratory animal models with implantation of synthetic mesh materials either alone or in combination with a composite hemostatic biomaterial. Both sterile and infected conditions were simulated. Tissue responses were evaluated by macroscopic assessment, histological examination, and semi-quantitative morphometric analysis at multiple time points. Results. Under sterile conditions, the composite-implant combination significantly reduced inflammatory cell infiltration, accelerated fibroblast proliferation, enhanced angiogenesis, and promoted the formation of mature connective tissue compared with implants used alone. In infected models, the combined approach markedly attenuated purulent inflammation, limited bacterial colonization, prevented excessive fibrotic encapsulation, and improved tissue integration.Conclusion. The findings demonstrate that the combined application of composite biomaterials and synthetic implants enhances biocompatibility, reduces infection-related complications, and improves regenerative processes. This strategy represents a promising approach for optimizing outcomes in minimally invasive surgery
Keywords: minimally invasive surgery; implant; experimental surgery